Evaluation of 11C‐choline positron emission tomography/computed tomography for determining treatment response in castration‐resistant prostate cancer patients. (25th July 2022) - Kimura, Kazuhiko; Kitajima, Kazuhiro; Kawanaka, Yusuke; Yokoyama, Hiroyuki; Komoto, Hisashi; Fujiwara, Masayuki; Furukawa, Yoshitaka; Kanematsu, Akihiro; Yamamoto, Shingo; Miyake, Hideaki; Yamakado, Koichiro
Abstract : Objective: The utility of 11 C‐choline positron emission tomography/computed tomography for determining treatment response as compared with prostate‐specific antigen response and prognosis prediction in castration‐resistant prostate cancer patients was investigated. Methods: Eighty‐four 11 C‐choline‐positron emission tomography/computed tomography scans before/after treatments with abiraterone ( n  = 12 patients), enzalutamide ( n  = 3), docetaxel ( n  = 9), cabazitaxel ( n  = 5), radiation therapy alone ( n  = 3), radiation therapy, enzalutamide, and/or abiraterone ( n  = 5), radium‐223 ( n  = 4), and radiofrequency ablation ( n  = 1) in 42 castration‐resistant prostate cancer patients were retrospectively examined. Prostate‐specific antigen values were determined before and after treatment. Using the Kaplan–Meier method, the correlation of Positron Emission Tomography Response Criteria In Solid Tumors with prostate‐specific antigen response and prognostic impact was evaluated. Results: Pretreatment 11 C‐choline‐positron emission tomography/computed tomography findings identified local, lymph node, bone, and visceral metastasis in 12, 12, 29, and five patients, respectively. Following treatments, complete metabolic response was noted in one, partial metabolic response in eight, stable metabolic disease in 13, and progressive metabolic disease in 20. Mean prostate‐specific antigen change for complete metabolic response, partial metabolic response, stable metabolic disease and progressive metabolic disease was −48.9%, −55.0% (range −92.4% to −19.1%), −4.2% (−33.2% to 35.1%), and 142.7% (30.7% to 373.8%), respectively, significantly greater in the progressive metabolic disease cases ( P  < 0.01). Positron Emission Tomography Response Criteria In Solid Tumors was well correlated with prostate‐specific antigen change. Patients with no progression (complete metabolic response/partial metabolic response/stable metabolic disease) showed significantly longer cancer‐specific survival than progressive metabolic disease ( P  < 0.005). Using pretreatment 11 C‐choline‐positron emission tomography/computed tomography results to divide into three groups; (a) local and/or lymph node metastasis without bone metastasis ( n  = 10), (b) <6 bone metastasis sites ( n  = 16), (c) ≥6 bone metastasis sites and/or visceral metastasis ( n  = 16), cancer‐specific survival showed significant stratification ( P  < 0.001). Conclusions: 11 C‐choline‐positron emission tomography/computed tomography may reflect castration‐resistant prostate cancer metastatic lesion activity for treatment response and prognosis evaluations.